2017
DOI: 10.18011/bioeng2017v11n1p26-36
|View full text |Cite
|
Sign up to set email alerts
|

ACÚMULO DE NUTRIENTES E MASSA SECA PRODUZIDA POR Crotalaria juncea CULTIVADA NO CERRADO

Abstract: A adubação verde com Crotalaria juncea é uma estratégia vastamente utilizada no Cerrado para melhorar as características químicas, físicas e biológicas do solo, em uma matriz que apresenta limitações naturais para o desempenho adequado dos cultivos. O objetivo do trabalho foi de verificar o acúmulo de nutrientes e produção de matéria seca por C. juncea cultivada em solo de Cerrado. Dois experimentos foram realizados nos anos de 2015 e 2016, em um Latossolo Vermelho distrófico, no município de Selvíria, MS, Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
1
1
1
Order By: Relevance
“…There was no significant interaction between the doses of Reactive Natural Phosphate (RNP) and the P accumulated in the green manure plants in the two years studied. The obtained results of P in the plants in the present study were higher than those found in other studies (XAVIER; OLIVEIRA; SILVA, 2017;SILVA et al, 2017), which are justified by the high production of dry mass and satisfactory weather conditions for the development of plants used as green manure (LEITE, 2018) and by the high P content in the soil (P: 37.9 mg dm -3 , Clay: 9.6%) at the beginning of the experiment.…”
Section: Resultscontrasting
confidence: 76%
“…There was no significant interaction between the doses of Reactive Natural Phosphate (RNP) and the P accumulated in the green manure plants in the two years studied. The obtained results of P in the plants in the present study were higher than those found in other studies (XAVIER; OLIVEIRA; SILVA, 2017;SILVA et al, 2017), which are justified by the high production of dry mass and satisfactory weather conditions for the development of plants used as green manure (LEITE, 2018) and by the high P content in the soil (P: 37.9 mg dm -3 , Clay: 9.6%) at the beginning of the experiment.…”
Section: Resultscontrasting
confidence: 76%
“…Considering this impact of fertilizers on the total energy used in the production of soybean, one way to reduce energy expenditure during production is to increase the efficiency of crop nutrient use. The increased efficiency of P and K fertilizer used (Teixeira, Silva, Sousa, Mattiello, & Soares, 2016), and of green fertilizers that promote nutrient cycling (Silva, Oliveira, Merloti, & Sá, 2017), and rooting promotion via co-inoculation with Bradyrhizobium and Azospirillum (Ferri, Braccini, Anghinoni, & Pereira, 2017) are examples of techniques that have been indicated to increase the efficiency of P and K use by soybean and thereby to increase EE. However, in terms of energy, one should be careful if opting to replace synthetic fertilizers by other sources of these elements.…”
Section: Resultsmentioning
confidence: 99%
“…Destaca-se ainda que as plantas de crotalária apresentaram elevado fator de transferência de K, P e Fe, devido aos altos teores de nutrientes na parte aérea desta planta. Segundo Silva et al (2017), a crotalária é eficiente na absorção de nutrientes, mesmo em solos pobres, superando teores de nutrientes em outras leguminosas e suprindo exigências nutricionais de plantas que serão cultivadas posteriormente e/ou em consórcio.…”
Section: Tratamentounclassified